2023
DOI: 10.1126/sciadv.adg9376
|View full text |Cite
|
Sign up to set email alerts
|

Quantum imaging of the reconfigurable VO 2 synaptic electronics for neuromorphic computing

Ce Feng,
Bo-Wen Li,
Yang Dong
et al.

Abstract: Neuromorphic computing has shown remarkable capabilities in silicon-based artificial intelligence, which can be optimized by using Mott materials for functional synaptic connections. However, the research efforts focus on two-terminal artificial synapses and envisioned the networks controlled by silicon-based circuits, which is difficult to develop and integrate. Here, we propose a dynamic network with laser-controlled conducting filaments based on electric field-induced local insulator-metal transition of van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…26−28,38−40 In fact, this LSPR phenomenon was induced by the localized free electrons from the metalized isolated VO 2 . Since the LSPR absorption was closely associated with the grain size or the meta surface, we just prepared different 3D VO 2 films by changing the deposition time (20,25,30 Figure 2E shows the UV−vis−IR spectra for the four 3D VO 2 samples at 370 K (after the phase transition). It was revealed that the absorption peak of the LSPR (the "valley" position) was very sensitive to the VO 2 island size; the larger the island size, the longer the wavelength for the absorption peak position.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26−28,38−40 In fact, this LSPR phenomenon was induced by the localized free electrons from the metalized isolated VO 2 . Since the LSPR absorption was closely associated with the grain size or the meta surface, we just prepared different 3D VO 2 films by changing the deposition time (20,25,30 Figure 2E shows the UV−vis−IR spectra for the four 3D VO 2 samples at 370 K (after the phase transition). It was revealed that the absorption peak of the LSPR (the "valley" position) was very sensitive to the VO 2 island size; the larger the island size, the longer the wavelength for the absorption peak position.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This specific transition dramatically alters its optical and electrical properties, making it widely used in functional optoelectronic devices. For example, many researchers have exploited VO 2 for various applications, including near-sensor computing, ASCII code encryption, neuromorphic computing, and optical switching . While the performance of a VO 2 -based device is not only closely associated with its phase transition property but also depends on its dimensional characteristics and grain size, especially for the infrared light or THz modulations with 3D-like VO 2 film or VO 2 meta-surface structures. Thus, the 3D dimension-induced spectrum modification in VO 2 film should have great potential to expand new applications.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, OES devices can induce multiple non‐volatile resistive states by only modulating the optical pulse width due to the time‐dependent plasticity, resembling photodetectors with memory functions. [ 53–54 ] This suggests the potential for parallel sensing, memorization, and learning of visual information in a single‐device platform (Figure 4f). To demonstrate the application of the OES device in optical communication, various patterns of optical signals are applied on the device, and the distinct postsynaptic current is recorded.…”
Section: Resultsmentioning
confidence: 99%
“…Neuromorphic devices that can simulate the working principle of the human brain have become a hot spot of cutting-edge research, and the key lies in the development of devices that mimic the behavior of neurons and synapses so as to construct a brain-like neural network. , In recent years, neuromorphic devices based on ferroelectric properties to simulate synaptic plasticity behavior have attracted greater attention, mainly driven by the natural advantages of ferroelectric materials in terms of low power consumption, nonvolatility, and antifatigue, which meet the requirements of neuromorphic computing for devices. It is well-known that the physical basis for the realization of functional properties of ferroelectric synaptic devices is the evolution of ferroelectric domains driven by external fields. Although much progress has been made in the development and macroscopic characterization of ferroelectric synaptic devices, , the microphysical picture of the domain dynamics for ferroelectric synaptic devices is still lacking.…”
mentioning
confidence: 99%